2011
DOI: 10.1159/000327149
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Parathyroid Hormone Levels and the Cardiorenal Metabolic Syndrome in Non-Diabetic Chronic Kidney Disease

Abstract: Aims: The relationship between parathyroid hormone (PTH) and the cardiorenal metabolic syndrome was examined among non-diabetic persons with chronic kidney disease (CKD). Methods: In a cross-sectional analysis, the relationship between PTH levels and the cardiorenal metabolic syndrome was investigated in 3,215 non-diabetic participants in the National Kidney Foundation-Kidney Early Evaluation Program (KEEP 2.0) found to have CKD (eGFR <60 ml/min/1.73 m2). Results: In unadjusted analyses, the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The KEEP database from November 1, 2005 through December 11, 2010 was examined. Since PTH levels were only measured among those with an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m 2 [18,19], the analysis was limited to this eGFR range among those with PTH and hemoglobin values recorded. Therefore, a total of 10,750 participants were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The KEEP database from November 1, 2005 through December 11, 2010 was examined. Since PTH levels were only measured among those with an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m 2 [18,19], the analysis was limited to this eGFR range among those with PTH and hemoglobin values recorded. Therefore, a total of 10,750 participants were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium, phosphorus, and intact PTH were measured as previously described [18,19]. Specifically, PTH was analyzed using the Immulite 2000 analyzer (Siemens Medical Solutions Diagnostics, www.usa.siemens.com).…”
Section: Methodsmentioning
confidence: 99%
“…An important evolving concept incorporates deranged phosphate metabolism in the pathogenesis of abnormalities characterizing the cardiorenal syndrome [12,19,20]. The current case report illustrates how abnormal phosphate metabolism can lead to systemic multiple organ disease including bone disease.…”
Section: Discussionmentioning
confidence: 95%
“…PTH also was found to be associated with MetS in other specific populations identified by diagnosis, age, gender or ethnicity. In one study, non-diabetic outpatients with chronic kidney disease (CKD) were associated with a higher prevalence of cardio-renal metabolic syndrome, and the prevalence of MetS increased as PTH increased, without associations with age or gender [22]. In a study of older American men, an inverse relationship was found between 25(OH)D and MetS, independent of Kalzium intake and PTH concentrations; in this population, as with the non-diabetic outpatients above, the odds for MetS increased as PTH increased.…”
Section: Variablesmentioning
confidence: 99%